207k views
2 votes
Given the following functions:

f(x)=x2
g(x)=x−3


Find the composition of the two functions and show your process:

f(g(x))

*** Caution: this is different from
g(f(x))

2. Given the following functions:

f(x)=x2
g(x)=x−3


Find the composition of the two functions and show your process:

g(f(x))


Caution: This is different from
f(g(x))

3. If the composition of two functions is:

1x−3


What would be the domain restriction? Describe how you found that answer.

User Hendi
by
5.2k points

1 Answer

2 votes

Answer:

1)
{\bf f }\circ {\bf g}(x) ={\bf x^2}-{\bf6x}+{\bf9} and
{\bf g }\circ {\bf f}(x)={\bf x^2}-{\bf3} are not equal

ie,
{\bf f} \circ {\bf g}(x) \\eq {\bf g} \circ{\bf f}(x)

2) The domain is x

Explanation:

Given functions are
f(x)=x^2 and
g(x) = x-3

now find the composition of two functions verify that


f \circ g = g {\circ} f

now find the composition of
f\circ g


f \circ g=f(g(x))


f \circ g=f(x-3)


f \circ g=(x-3)^2


f \circ g=x^2-2(x)(3)+3^2


f \circ g=x^2-6x+9

now find the composition of
g \circ f


g \circ f=g(f(x))


g \circ f=g(x^2)


g \circ f=x^2-3

Comparing the above two compositions we get


f \circ g = x^2-6x+9 and
g \circ f= x^2-3 are not equal

ie,
f \circ g \\eq g \circ f.

2) Given that the composition of two function is x-3

Let the functons be f(x) and g(x)

so the composition of two function
f \circ g=x-3

it may be written as
f(g(x))=x-3


g(x)=f^(-1)(x-3)


g(x)=x-3

User Kieran
by
5.1k points